A gamificação nos processos sociais contemporâneos - NAVARRO, João Rafael Ersina (2016)
The conception of gamification applied to contemporary social processes is very new, once the strong presence of media now offers the necessary features for an effective project since the second half of the last decade through new, convergent and interactive interfaces. The main object of this study is the conceptualization of gamification, its affinities and differences with electronic games, its audiovisual resources and its immanence in contemporary social processes. The result will be a study of the current conditions and the effects of gamification. This study is based on a methodology that studies data research and applications. Among them, we can highlight Waze, which will be a case study in this dissertation because of its large base of active users, which favors the collection of data at different levels. The use of the game and its importance to contemporary age have been studied by important theorists such as Brougère, Bruhns, Duflo, Freire, Piaget, Schiller, among other authors. This study was developed based on considerations of Pierre Levy, Henry Jenkins and Kevin Werbach about social networking, convergence culture and collective intelligence, taking into account the comments of Johan Huizinga, on the fundamental aspects of the games.